Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2008
DOI: 10.1007/s00299-008-0625-7
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of cytoplasmic male sterility of rice with Lead Rice cytoplasm in comparison with that with Chinsurah Boro II cytoplasm

Abstract: Rice with LD-type cytoplasmic male sterility (CMS) possesses the cytoplasm of 'Lead Rice' and its fertility is recovered by a nuclear fertility restorer gene Rf1. Rf1 promotes processing of a CMS-associated mitochondrial RNA of atp6-orf79, which consists of atp6 and orf79, in BT-CMS with the cytoplasm of 'Chinsurah Boro II'. In this study, we found that LD-cytoplasm contained a sequence variant of orf79 downstream of atp6. Northern blot analysis showed that atp6-orf79 RNA of LD-cytoplasm was co-transcribed and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
50
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(55 citation statements)
references
References 15 publications
3
50
1
Order By: Relevance
“…We suggest that the different RNA binding activity observed in this study may be due to the differences between the intragenic sequences of atp6-orf79 and atp6-orfH79. In LD-CMS rice, LD-atp6-orf79 is an orthologous gene associated with CMS, yet restoration can occur with either Rf1 or Rf2 (Itabashi et al, 2009). Rf2 encodes a GRP with a mitochondrial presequence, suggesting that a divergent restoration pathway may exist even within the same CMS system.…”
Section: A Coordinated Model Of the Functions Of Rf5 And Grp In Hl-cmmentioning
confidence: 99%
“…We suggest that the different RNA binding activity observed in this study may be due to the differences between the intragenic sequences of atp6-orf79 and atp6-orfH79. In LD-CMS rice, LD-atp6-orf79 is an orthologous gene associated with CMS, yet restoration can occur with either Rf1 or Rf2 (Itabashi et al, 2009). Rf2 encodes a GRP with a mitochondrial presequence, suggesting that a divergent restoration pathway may exist even within the same CMS system.…”
Section: A Coordinated Model Of the Functions Of Rf5 And Grp In Hl-cmmentioning
confidence: 99%
“…In rice, ORF79 is a stable membrane-integrated polypeptide expressed in all tissues. In a line of CMS rice carrying a variant of orf79, termed L-orf79, the L-ORF79 polypeptide is not detected [100]. Itabashi et al [100] suggested that this might be due to a sequence alteration in the 5 untranslated region that prevents translation.…”
Section: Why Do Most Of the Unique Orfs Not Matter In Angiosperm Mitomentioning
confidence: 99%
“…In a line of CMS rice carrying a variant of orf79, termed L-orf79, the L-ORF79 polypeptide is not detected [100]. Itabashi et al [100] suggested that this might be due to a sequence alteration in the 5 untranslated region that prevents translation. However, it is also possible that a Glu to Ala substitution in the coding region may alter the higher-order structure, making L-ORF79 accessible to the degradation system.…”
Section: Why Do Most Of the Unique Orfs Not Matter In Angiosperm Mitomentioning
confidence: 99%
“…BT-CMS originated from the indica variety of Chinsurah boro II ( Shinjyo 1975 ) and has been studied most extensively in rice ( Iwabuchi et al 1993, Kazama and Toriyama 2003, Wang et al 2006. The LD-CMS line originated from the Burnese cultivar Lead Rice ( Watanabe 1971, Itabashi et al 2009 ). As a result, we found that the OsNek3 mRNA expression level was extensively reduced in the CW-CMS line as in our previous microarray ( Fig.…”
Section: Osnek3 Mrna Expresssion Is Suppressed Under a Cms Backgroundmentioning
confidence: 99%